California Teamsters Public Professional and Medical Employees Union, Local 911 Newsletter (1976)
The October 1976 newsletter of the California Teamsters Public, Professional and Medical Employees Union, Local 911 highlights an exclusive interview with Senator John V. Tunney, who discusses aerospace jobs, public employee union rights, federal spending, and support for public safety workers. It reports a $20,000 legal victory securing educational incentive pay for Fountain Valley firemen and outlines important labor developments, including Supreme Court decisions affecting public employees and discussions of final-offer arbitration. The issue features union organizing successes, contract negotiations at McDonnell Douglas, layoff grievances, and expanded representation efforts in Nevada and San Diego. Additional articles cover legislative updates, member benefits such as a new insurance plan and discount program, and the awarding of a $4,000 scholarship to a member's daughter